Biology of the pineapple root borer Sufetula anania (Lepidoptera: Crambidae) - Méndez-Leiva, William (2025)
Introduction. Fresh pineapple production in Costa Rica is a profitable economic activity that is carried out in the Huetar Norte Region; it is recently affected by a new pest, Sufetula anania Solis and Hayden (Lepidoptera: Crambidae) which causes damage to the plant, with the capacity of destroying the root system. Objective. To determine the life cycle and ecology of the root borer S. anania in pineapple cultivation in the Northern Zone of Costa Rica. Materials and methods. The study was carried out in the laboratory of Research and Development, of Agroindustrial Piñas del Bosque Company, San Carlos, Costa Rica. Main biological aspects, life cycle and biometric parameters were determined and a breeding methodology was developed. Results. S. anania has a life cycle composed of 4 stages of development (egg, larva, pupa and adult) and is completed between 29 and 70 days; the duration in days of each life cycle stage was: eggs (7.10 ± 0.02), larvae: L1 (3.10 ± 0.31), L2 (2.20 ± 0.48), L3 (2.77 ± 0.57), L4 (4.53 ± 1.72), L5 (11.30 ± 2.71), pupae (8.63 ± 1.3), adults: female (7.29 ± 2.65) and male (5.25 ± 4.27). The laboratory breeding methodology was based on stem sections of vegetative pineapple suckers. Conclusion. S. anania can complete 6 to 12 life cycles per year depending on climatic conditions and food availability. During feeding, the larvae generate tunnels within the plant tissues that serve as places of refuge and protection.